The pamphleteer Ephippus of Olynthus, King Alexander, and the Persian Royal Hunt - Spawforth, Antony J. S. (Histos, 2012)
This paper argues that Jacoby’s fragment 5 of Ephippus of Olynthus’ lost pamphlet on the deaths of Hephaestion and Alexander conceals a malevolently distorted and hitherto unrecognized reference to Alexander’s adoption in 324/323 BC of the traditional hunting style of the Assyrian and Achaemenid kings, namely, the use of a chariot and archery in pursuit of lions. The paper puts this startling development into the larger context of, firstly, Alexander’s political and cultural Persianizing, and, secondly, the rich symbolism of the royal lion hunter in the ancient Near East. Finally, the paper asks how far such ‘misreadings’ of the historical Alexander’s Asian monarchy by the first generation of Greek Alexander-historians might have colored the later ancient view of Alexander’s alleged quest for deification.